Transparency for Impact : Lessons from IFC Projects in Peru’s Natural Resources Sector - International Finance Corporation (International Finance Corporation, Washington, DC, 2020)
The natural resources sector, particularly the mining industry, has been a significant part of Peru’s economic growth over the past decade. The law mandates that the national government transfer half of the income taxes paid by mining companies to regional and local governments. This transfer of funds represents a significant opportunity to respond to the needs of local communities and lift them out of poverty. The Peruvian law of transparency and access to public information lays out mandatory compliance rules for public authorities and officials. It requires public entities at the national, regional, and municipal levels to deliver, in a timely manner, information requested by people and entities and to provide adequate infrastructure to systemize and publish public information. International Finance Corporation (IFC) identified five groups of stakeholders that were key in promoting transparency and accountability: authorities and municipal officials; local leaders; surveillance committees of the participatory budgeting process; the media; and the general population. Implementation of IFC’s transparency and accountability projects in Peru generated a wealth of information, experience, recommendations, and lessons that will be useful when designing and implementing future interventions.